Answer:
(m, n) = (
, -
)
Explanation:
given the 2 equations
m - n = 3 → (1)
2m + 3n = 4 → (2)
rearrange (1) expressing m in terms of n by adding n to both sides
m = 3 + n → (3)
substitute m = 3 + n into (2)
2(3 + n) + 3n = 4
6 + 2n + 3n = 4
6 + 5n = 4 ( subtract 6 from both sides )
5n = - 2 ( divide both sides by 5 )
n = -
![(2)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t0uv673spbc3c31ajeld1inwaddg10eja3.png)
substitute this value into (3)
m = 3 -
=
![(13)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8utoocs5m652xzzmh53tt2vil3l7pynk1b.png)